2020
DOI: 10.1111/jop.13114
|View full text |Cite
|
Sign up to set email alerts
|

Increased odds ratio for COVID‐19 in patients with recurrent aphthous stomatitis

Abstract: The ACE2 receptor, the binding sites for the COVID‐19, is expressed abundantly in the oral cavity, raising the question of whether the mouth is a target for the virus in addition to organs such as kidneys and lungs. Recently, a flurry of individual case reports on oral manifestation of COVID‐19 including ulceration, blistering lesions, and stomatitis were published. However, it is not clear whether the oral presentations that are not unique to the virus are indeed related to the virus and appear at a higher pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 11 publications
2
35
0
8
Order By: Relevance
“…One study only reported recurrent aphthous stomatitis in COVID-19 patients, and one study reported oral changes but failed to describe the type of changes noted. 10 , 11 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study only reported recurrent aphthous stomatitis in COVID-19 patients, and one study reported oral changes but failed to describe the type of changes noted. 10 , 11 …”
Section: Resultsmentioning
confidence: 99%
“…There was only one study in this review where there was a comparator group: patients with recurrent aphthous ulceration and COVID-19 as compared to patients with COVID-19 without recurrent aphthous ulceration. 11 This study only focused on recurrent aphthous ulceration, which limits its scope in determining the causal link to various other types of lesions. Nevertheless, they stated a strong association between COVID-19 and recurrent aphthous stomatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Santos et al (2020) e Ansari et al (2020) even healthy patients who are affected by Covid-19 may present these oral manifestations, but pointing out hypotheses whether it is a result of strong direct viral infection or decreased immune response capacity of the patient that could open the door to opportunistic infections and also to pharmacological treatments performed. According to Katz and Yue (2021) there is higher prevalence of recurrent aphthous stomatitis in patients confirmed with Covid-19 than in healthy patients. Xu et al (2020) point to the oral cavity as a target for novel coronavirus, explained by the wide distribution of receptors in the oral tissues and the spectrum of changes published in the literature associated with Covid-19 including aphthous and vesicular ulcerations (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On reviewing the currently growing evidence on aphthous stomatitis of COVID-19 patients, we have found 22 cases reported in 8 publications (7 case reports, 1 prevalence study). [5][6][7][8][9][10][11][12] Fourteen cases (63.6%) were from Americas, five (22.7%) from Europe, two (9%) from the Middle East, and one (4.5%) from Asia-Pacific ( Table 2). The aphthous lesions were equally distributed across gender; however, female predominance was noticed in the prevalence study of Florida, which is similar to our series.…”
Section: Sars-cov-2) and Aphthousmentioning
confidence: 99%